Clinical and Urodynamic Results of Repeated Intradetrusor Onabotulinum Toxin A Injections in Refractory Neurogenic Detrusor Overactivity: Up to 5 Injections in a Cohort of Children With Myelodysplasia - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TARCAN, TUFAN; TANIDIR, YILÖREN (ELSEVIER SCIENCE INC, 2018)
OBJECTIVE To determine the efficacy and safety of repeated intradetrusor onabotulinum toxin A (onaBoNT-A) injections in children with neurogenic detrusor overactivity due to myelodysplasia. MATERIALS AND METHODS The study group consisted of 19 children (4 boys and 15 girls) with a mean age of 10.3 +/- 3.1 years old, who had received at least 2 injections of 10 U/kg onaBoNT-A for the treatment of urinary incontinence resistant to anticholinergic treatment and clean intermittent catheterization in our clinic, between 2010 and 2015. Controlled urodynamic studies were performed at the baseline and 3 months after each injection. RESULTS Eight of the children received 3 injections, 5 children had 4 injections, and 2 children had 5 injections. From the baseline to the fifth injection, the detrusor compliance (1.3, 4.5, 10, 20.7, 18.8, and 16.6 mL/cm H2O), the maximum bladder capacity (82.0, 157.0, 191.0, 272.0, 299.0, and 210.5 mL), and the maximum detrusor pressure (55.0, 33.0, 22.0, 12.5, 16.0, and 12.5 cm H2O) were assessed. The findings significantly improved following the first, second, and third injections, when compared with the previous bladder dynamics (P <. 05), but the differences with the fourth were not statistically significant (P >. 05). The continence periods were similar under clean intermittent catheterization after all of the injections (P <. 05), and no severe side effects were observed. CONCLUSION Repeated onaBoNT-A injections are a safe treatment modality and can be offered as an effective alternative choice, instead of more invasive surgery, in children with neurogenic detrusor overactivity due to myelodysplasia. (C) 2017 Elsevier Inc.
Keywords: BOTULINUM-A TOXIN; INTRAVESICAL CAPSAICIN; BLADDER; HYPERREFLEXIA; NEUROTOXIN